An Essay on Concept and Essencials of Acclimatization - Wada, Shunji (1955)
On what conditions should acclimatization-theory be established as a science?. In analyzing the concept of acclimatization scientifically, we are several prevailing interpretation of the concept but cannot find an overal established and accepted interpretation of the concept.